Delivering Energy Efficiency in the Middle East and North Africa : Achieving Energy Efficiency Potential in the Industry, Services and Residential Sectors - World Bank Group (World Bank, Washington, DC, 2016)
The main objective of this report is to provide an intermediate step toward building more energy-efficient economies in the Middle East and North Africa (MENA) region. The present study complements the 2009 Energy Sector Management Assistance Program (ESMAP) report by providing a quantitative basis for sectoral targeting and focusing on delivery mechanisms. Taking advantage of the results of the Regional Center for Renewable Energy and Energy Efficiency (RCREEE) and preliminary results of the Readiness for Investment in Sustainable Energy (RISE) World Bank Survey, the report is able to assess the areas where countries in MENA can gain most from the energy efficiency (EE) potential and build an enabling environment for enhancing EE. Finally, the report draws on lessons learned on EE from other middle-income and high-income countries and brings in perspectives that can serve as beneficial for the MENA countries. The report focuses primarily on the three most electricity intense end use sectors: the industry, services, and residential sectors. For many countries in the MENA region, electricity shortages—often connected to the cost and availability of imported fuels—are key motivators for raising EE. This book is arranged as follows: 1) Chapter one seeks to provide a quantitative basis for considering EE priorities; 2) Chapter two presents a comprehensive, integrated framework to support EE; 3) Chapter three draws on examples from other regions of how energy savings have already been delivered through mechanisms involving two classes of agents—energy utilities and domestic finance institutions—whose participation is key to scaling up EE; and 4) Chapter four combines the information in the previous three chapters, and offers options for how to enhance EE in the MENA region.